2019
DOI: 10.25200/bjr.v15n3.2019.1219
|View full text |Cite
|
Sign up to set email alerts
|

Fake news: emotion, belief and reason in selective sharing in contexts of proximity

Abstract: This text addresses the phenomenon of so-called fake news in the new media ecosystem, namely in contexts of increasing influence of populist discourse and action, such as Brazil, the UK, the USA, Italy, among others. It does so by way of some characteristics already implicit in the limited effects theory: a) fake news involves, in a specific way, the participation of its receivers in disseminating and sharing it; b) producers/consumers (prosumers) are involved in contexts of proximity that facilitate selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…They concluded that media played a little role in the public opinion. This idea follows similar recent studies (Correia, Jerónimo & Gradim, 2019), proposing that the agenda setting theory is completely outdated. The text that is followed deals with the concept of "information bubbles", as media engage with audiences to filter public perceptions.…”
mentioning
confidence: 56%
“…They concluded that media played a little role in the public opinion. This idea follows similar recent studies (Correia, Jerónimo & Gradim, 2019), proposing that the agenda setting theory is completely outdated. The text that is followed deals with the concept of "information bubbles", as media engage with audiences to filter public perceptions.…”
mentioning
confidence: 56%
“…Similarly, Vosoughi et al (2018) claim that circulating fake news aims to disseminate a thrilling and sensational headline and seek attention. Correia et al (2019) has also supported this concept stating that one of the aims to share fake news is to create a drama and surprise the audience with something they were not expecting in a regular setting. Bright (2016) stated that another aim of sharing fake news is to increase the social reputation and increase a person's social status.…”
Section: Sources and Aims Of Fake Newsmentioning
confidence: 94%
“…Disinformation is not new in the field of journalism [Tandoc, Lim & Ling, 2018] or science [Marleau & Girling, 2017]. Its increase has been associated with the emergence of a new, more fragmented media ecosystem that allows content to be personalized and customized according to audience interest, regardless of whether that content is factual or not [Correia, Jerónimo & Gradim, 2019;Swire-Thompson & Lazer, 2020]. The effects of disinformation are further enhanced by political polarization [Aruguete & Calvo, 2020] and communication devices by populist governments, usually on the extreme right [Hameleers, 2020].…”
Section: The Public Problem Of Disinformationmentioning
confidence: 99%